Evaluation of Training on Teaching Methodology & Assessment of the Teachers of different Medical Colleges in Bangladesh - Tapu, Thanadar Tamjeeda; Talukder, Md Humayun Kabir; Flora, Thanadar Ajmiree; Barman, Neela (Bangladesh Journal of Medical Education, 2026)
Background: With the evolution of healthcare needs for the community and the changing trends in medical education in the 21st century, medical teachers need to be prepared for their tasks in the coming decades. Although many reports describe various faculty development interventions, there is a very few research indicating their effectiveness. Objective: To find out the impact of training programme on teaching methodology and assessment in medical education. Methods: This mixed method study was carried out in different medical and dental colleges of Bangladesh during the period of July 2024 to June 2025. A pretested self-administered semi-structured questionnaire was administered upon medical teachers and 10 medical teachers were selected from different medical colleges of Bangladesh for in depth interview. Results: This study revealed that out of 331 medical teachers 95% received formal training/course in Teaching Methodology & Assessment. Of them around 78% received offline training, more than 91% received training on Teaching Methodology & Assessment and around 80% received training from Centre for Medical Education (CME). Near 58% medical teachers responded that most of the times the objectives of the session were prepared according to SMART criteria, more than 50% responded that SGT was interactive, around 44% responded that teachers prepared lesson plan. Most of the medical teachers (78%) responded that integrated teaching and learning was practiced. Regarding assessment, teachers were satisfied in learning different tools for assessment. Medical teachers responded regarding different issues related to teaching methodology and assessment and also some challenges and barriers to implement them with recommendations. Conclusions: Training on teaching methodology and assessment appear highly valued by participants, who also report changes in behavior. Nevertheless certain limitations may affect the effectiveness of the research work. Further research to explore these associations and outcomes, at the individual and organizational level, is required to explore in-depth. BJME: Vol.-17, Issue-01, January, 2026:19-33